The Effect of Brown Algae Sargassum sp. Extract Towards The Amount of Macrophages in The Healing Process of Traumatic Ulcer - Annisa Rahmawati; Agni Febrina Pargaputri; Isidora Karsini S (Denta Journal Kedokteran Gigi, 2018)
Background: The Sarggasum’s sp. extract contains of several chemical properties such as flavonoid, vitamin A, vitamin C, zinc, and calcium which has benefit as anti-inflammation, so it can be used as an alternative therapy for traumatic ulcer. Purpose: To investigate the effectivity of Sargassum’s sp. extract towards the amount of macrophages in the healing process of traumatic ulcers. Material and Method: 32 wistar rats were divided into 4 groups, K1 the negative control group without treatment, K2 the positive control group with the drugs containing 0.2% hyaluronic acid, and the treatment group K3 Sargassum’s sp. extract concentrations of 50% and K4 Sargassum’s sp. extract concentrations of 75%. Traumatic ulcer were made in the labial mucosa of rats by using heated amalgam stopper. On the fourth and seventh day, rats were sacrified and biopsied on lower labial mucosa. The macrophages were observed using a 1000x magnification light microscope with OptiLab viewer. Result: The statistical test using One Way ANOVA showed significant difference (p<0,05) of macrophage on fourth day group. The LSD test showed a significant difference (p<0,05) in macrophages at K1 (2.83±1.03) compared to K3 (1.17±0.64), K1 compared to K4 (0.58±0.79), K2 (2.58±0.50) compared to K3, and K2 compared to K4 at the fourth day group, whereas the seventh day group showed no significant differences between each groups. Conclusion: The Sargassum’s sp. extract concentrations of 75% is the most effective in decreasing amount of macrophages in the healing process of traumatic ulcers.